Moringa leaf (Moringa oleifera L) flavonoids utilization in suppressing growth of Aedes aegypti larvae - Vinsensius Manek Ati; Ermelinda D. Meye; Refli Refli; Alfred O.M. Dima; Djeffry Amalo; Ursula Luhur Jebatu (Jurnal Sains dan Terapan Kimia, 2022)
The study was conducted to determine the potential use of Moringa leaf flavonoids as biolarvicides in suppressing the growth of Aedes aegypti mosquito larvae. The design used was a completely randomized design (CRD) with six flavonoid treatments including P0 (0 ppm flavonoids as a negative control), P1 (12.5 ppm flavonoids), P2 (25 ppm flavonoids), P3 (50 ppm flavonoids), P4 ( flavonoids 75 ppm), and P5 (flavonoids 100 ppm). Each treatment was repeated three times. The results of the analysis of diversity (Anova) revealed that Moringa leaf flavonoids had a very significant effect (P = 0.000) on the mortality of A. aegypti mosquito larvae. The administration of 50 ppm flavonoids of Moringa leaf extract caused the mortality of A. aegypti larvae to reach 95%, and at a concentration of 75 ppm, it increased the mortality percentage to 100%. The results of the probit analysis showed that the lethal concentration 50 (LC50) was achieved at a concentration of 7.96 ppm with exposure for 24 hours, while the lethal concentration-time 50 (LT50) at a concentration of 75 ppm was achieved in a shorter time (2.08 hours).  Keywords: flavonoids, moringa leaf, Aedes aegypti, biolarvacide